Model Pembelajaran Inkuiri Terhadap Hasil Belajar IPA Siswa Sekolah Dasar - Bria, Maria Demetriana; Popiyanto, Yudha; Larasati, Diyas Age (Trapsila: Jurnal Pendidikan Dasar, 2021)
Abstract The artikel is prospered to know effectively in the incubaton model of student’s learning. One of the problems in the learning process is students who have low grade in the classroom. The cause is that students are less active in learning, and also teachers who often teach without a model or method and therefore make itbdifficult for student to understand the model used in learning.In this method student is encouraged to be always involed and active learning. How was  always actively asking for any material that was presented to her teachers. And the quedtions don’t always have to be answered by the teacher. Because all students have same opportunity. For gave the answer to any questions asked by the teacher this incubaton model could incrase the student learning rwsult because studrns always have to search for the marks themselves the answer to any common problem. The system provided by will be more critical daam thinks this substion will be the more meaning, the roots which will always be understand and all students remember.Keywords: inquiri learning model, Learning Outcomes.